The Relationship Of Brand Image And Product Quality With Consumer Behavior In Buying Lifebuoy Soap At Zan Mart Manna Shop, Bengkulu Selatan - Heri Yeni Susanti; Ahmad Soleh; Abdul Rahman (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine a correlation between brand image and product quality with consumer behavior in buying lifebuoy soap at Toko Zan Mart Manna of South Bengkulu. The sample in this study was 50 people who bought lifebuoy soap and sampling technique used is accidental sampling technique. Data collection methods by using questionnaire and analytical methods used are Spearman rank correlation and hypothesis testing. Brand image has a strong correlation with consumer behavior in buying Lifebuoy Soap at Toko Zan Mart Manna of South Bengkulu with a correlation value of 0.655, meaning that the higher of brand image perceived by consumers, the higher consumer behavior in buying Lifebuoy Soap at Toko Zan Mart Manna of South Bengkulu. This result is strengthened by the results of the hypothesis test that t count is greater than t table (6.005 > 1.677). This means that brand image has a significant correlation with consumer behavior in buying Lifebuoy Soap. Spearman rank correlation for the relationship of product quality with Consumer Behavior Buying Lifebuoy Soap at Toko Zan Mart Manna of South Bengkulu has a very strong correlation with value of 0.863, this means that the more quality of lifebuoy soap products, the higher the Consumer Behavior in Buying Lifebuoy Soap. This is reinforced by the results of the hypothesis test that t count is greater than t table (11,840 > 1,677). This means that product quality has a significant correlation with consumer behavior in buying Lifebuoy Soap at Toko Zan Mart Manna of South Bengkulu.